THE POPHAM ARBORETUM: A REFUGE FOR GREY SLENDER LORIS (Loris lydekkerianus) IN AN URBANIZED LANDSCAPE IN SRI LANKA - WEERARATHNE, W. A. P. P.D.; Wijesinghe, M.R. (My University, 2019)
The aim of the present study was to document the population size, distribution and habitat preferences of the Grey Slender Loris (Loris lydekkerianus) in the Popham Arboretum in Dambulla, Sri Lanka. The Popham Arboretum is a small and isolated forest patch nestled in an urbanized landscape that serves as a refuge for L. lydekkerianus. The study was carried out over 15 nights for a period of ten months from September 2016 to June 2017, with nocturnal searches being conducted between 1900 to 2200 hrs. A total of 55 sightings were made, with the number of sightings per night ranging from one to eight. The sightings suggest that the arboretum supports a population of at least 15 individuals. The loris was more frequently sighted in core areas of the arboretum than towards the edges, with preference shown for areas which were relatively cooler and secluded. Furthermore, the lorises were sighted in areas with greater canopy cover and a higher richness of trees, shrubs and woody creepers. Two species, a tree Diplodiscus verrucosus and a woody climber Derris parviflora, were selectively used by the lorises. Our findings highlight the possible dangers of urban expansion on this arboreal primate and the need to strengthen its protection within the arboretum.
Keywords: Popham Arboretum, Loris, habitat selection, edge effects